Ultraschalldiagnostik bei muskuloligamentären Verletzungen sowie Insertionstendinopathien am Ellenbogengelenk = Ultrasound diagnostics for myotendinous injuries and insertiontendinopathies of the elbow joint - Doll, Julian; Fischer, Christian (Der Radiologe, 2018)
IntroductionAcute capsular injuries of the elbow joint and its ligaments predominantly occur after joint dislocation or subluxation. Together with lateral and medial epicondylitis they represent a common injury pattern in radiology, orthopedic and trauma surgery.Clinical issueBecause of the complexity of the elbow joint, knowledge of the elbow dislocation and injury pattern as well as the anatomy is essential in order to adequately estimate the injury severity and joint stability. This is crucial for the correct diagnosis and choice of treatment. Systematic physical examination and careful radiographic evaluation are components of an adequate management of acute soft tissue elbow injuries.Diagnostic work-upThe cost-effective ultrasound has emerged as a useful imaging modality for the diagnosis of acute joint and soft tissue pathologies especially in the acute phase after injury. Ultrasound as a diagnostic tool enables visualization of motion sequences during dynamic examination and therefore a better understanding of pathologies. Ultrasound examinations of the most common injuries of the elbow joint are presented in this overview.
Gesehen am 09.04.2019